Quantitative Evaluation of Myocardial Stress/Rest 201TISPECT: Results of a ROI-Based Method in 108 Patients with CHD - Buell, U.; Stirner, H.; Dahl, J. vom; Uebis, R.; Kleinhans, E.; Biedermann, M.; Große, W.; Simon, H. J. (Nuklearmedizin - NuclearMedicine, 1987)
ROI-based polar maps (33 ROIs) were employed to evaluate quantitatively stress/rest myocardial 201TI SPECT in 108 patients with angiographically proven coronary heart disease (CHD) in comparison with 30 controls. Sensitivity in detecting a CHD with stenoses of > 50% of luminal diameter was determined versus normal regional values (± 2.5 SD) employing vitality (VI) and wash-out corrected redistribution (RD). The method was evaluated referring to the severity of the disease, to the number of ROIs displaying changes [(a) 1 ROI, (b) >2 ROIs], to validity of VI, RD or a combination thereof, and for specificity. Wash-out values were found to depend on degree of stress individually achieved and thus were not used as a threshold criterion. Sensitivity in supply areas with old myocardial infarctions was 95% (a) and 86% (b), resp. With no infarction, it was 96% (a) and 79% (b), resp. VI in stenosis > 75% was more sensitive than RD. However, combined evaluation of VI and RD yielded sensitivities from 91-100% (a) and 77-94% (b), resp. for different main supply areas. In stenosis < 50% with normal VI, RD was positive in 18-31 %. Specificity turned out to be 91 % (a) and 97% (b), resp. We conclude that the method presented is reliable to quantify numerically 201TI kinetics in myocardial SPECT, aimed at detecting and describing CHD.33 Regions of Interest (ROIs) in polarer Anordnung wurden verwendet, um quantitative Befunde der Belastungs/Ruhe-SPECT des Myokards mit 201TI bei 108 Patienten mit koro- narangiograpisch gesicherter koronarer Herzkrankheit (KHK) und bei 30 Normalen vergleichend zu bewerten. Die Sensitivität bei der Erfassung von Stenosen >50% wurde im Vergleich zu regionalen Normwerten (± 2,5 SD) mittels der Vitalität (VI) und der Wash-out-korrigierten Rückverteilung (RD) bestimmt. Die Methode wurde unter Bezug auf Schwere der Erkrankung, Zahl veränderter ROIs [(a) 1 ROI, (b) >2 ROIs], Wertigkeit von VI, RD bzw. deren Kombination, und auf die Spezifität bewertet. Wash-out-Werte zeigten sich abhängig vom individuellen Belastungsgrad und wurden daher nicht als Schwellwert verwendet. In koronaren Versorgungsgebieten mit alten Infarkten betrug die Sensitivität 95% (a) bzw. 86% (b). Ohne Infarkt waren es 96% (a) bzw. 79% (b). Bei Stenosen >75% war VI sensitiver als RD. In der Kombination ergaben sich für die verschiedenen koronaren Hauptversorgungsgebiete Sensitivitäten von 91-100% (a) oder von 77-94% (b). Stenosen <50% mit normaler VI waren zu 18-31% mit erhöhter RD verbunden. Die Spezifität errechnete sich mit 91% (a) bzw. 97% (b). Die vorgestellte Methode erwies sich als verläßlich bei der numerischen Quantifizierung der 201T1-Kinetik mit der Myokard-SPECT, gerichtet auf die Entdeckung und Beschreibung einer KHK.